Gene therapy and editing in the treatment of hereditary blood disorders: Medical and ethical aspects. (September 2022) - Cano Alburquerque, Paula; Gómez-Tatay, Lucía; Aznar, Justo
Gene therapy and gene editing are revolutionising the treatment of genetic diseases, most notably haematological disorders. This paper evaluates the use of both techniques in hereditary blood disorders. Many studies have been conducted in this field, especially with gene therapy, with very promising results in diseases such as haemophilia, certain haemoglobinopathies and Fanconi anaemia. The application of these techniques in clinical practice and the foreseeable development of these approaches in the coming years suggest that it might be useful to evaluate the results achieved thus far. It is also essential to reflect on the possible bioethical concerns raised by the use of both techniques, especially in terms of safety issues for patients, potential side effects, treatment duration, accessibility and cost of treatment, and the heritability of genetic changes produced if germline cells are used.